Effects of the exhaust gas heat recovery system with a plate heat exchanger on the warm-up performance characteristics of the gasoline engine - JungKim, Chan; Wook-Han, Sank; Hyun Kim, Ki; Yeon Lee, Moo; Soo Lee, Gee (International Journal of Engineering and Technology, 2018)
Background/Objectives: To meet the regulations for the fuel economy, an EHRS (Exhaust gas Heat Recovery System, which was installed within the vehicle exhaust system and recovered the heat from the exhaust gas, were needed. The EHRS enabled the engine to achieve the fast warm-up performance for reducing friction loss during the cold start.The objective of this paper was to investigate the effects of the design parameters of the EHRS with a plate heat exchanger on the warm-up performance of a gasoline engine.Methods/Statistical analysis: The EHRS with the plate heat exchanger was manufactured and installed behind the catalyst in the exhaust system of the gasoline direct injection engine. The experimental study and multi-disciplinary analysis were carried out to investigate the effects of the EHRS on the warm-up performance of the engine, such as the coolant temperature, the exhaust gas temperature and the recovery heat at idle condition and the step-load condition.Findings: Because the recovery of heat was about 1. 7 kW at idle condition, the effect of the EHRS on the warm-up performance was negligible. However, due to 17.2 kW of the recovery of heat at the stepload condition of T=140 Nm at N=2,400 rpm, the EHRS enabled to shorten the warm-up time by 548 s comparison that of the base engine.Improvements/Applications: The fuel economy will be expected to be improved through an EHRS, which provides the improved combustion in the warm-up phase and a decrease in friction loss.Â Â